Osteoarticular tuberculosis cases in the southwest of China: A 9-year retrospective study - Wang, Dong-Mei; An, Qi; Yang, Qing; Liao, Yi; Jian, Yao (Frontiers in Medicine, 2023)
Background Osteoarticular tuberculosis (TB) is an uncommon form of extrapulmonary TB. In this study, we analyzed the epidemiological characteristics, common sites, and drug resistance profiles of osteoarticular TB infections occurring in southwest China. Methods A total of 3,254 cases of patients clinically diagnosed with osteoarticular TB infections between 2013 and 2021 were retrospectively analyzed. Patients' demographic and clinical characteristics were collected. Drug sensitivity testing was performed using the microporous plate ratio method. Chi-squared analysis was used to analyze the rates of and trends in mycobacterial isolates. Results Of the 3,254 patients, 1,968 (60.5%) were men and boys, and 1,286 (39.5%) were women and girls; patients' ages ranged from 1 to 91 years, with an average of 42 ± 19.3 years. In terms of disease, 2,261 (69.5%) had spinal TB, mainly thoracic (815, 36%) or lumbar (1,080, 48%); joint TB was found in 874 cases (26.9%), mainly occurring in the knee (263, 30%) or hip (227, 26%); and both spinal and joint TB were observed in 119 cases (3.7%). Drug susceptibility tests were performed on 241 isolated strains of MTB; 70 strains (29.0%) were resistant to at least one drug, and MDR-TB and XDR-TB were observed in 7.1 and 1.2% of strains, respectively. Conclusions In southwest China over this period, osteoarticular TB mainly affected middle-aged and young men with poor nutritional status. Patients from ethnic minority areas also accounted for a large proportion of cases. Spinal TB is prone to occur in the lumbar and thoracic vertebrae, and joint TB is prone to occur in the lower limb joints. Additionally, there has been an increasing trend in the number of TB cases over the past 9 years, and drug resistance has also increased.